Mediating effects of loneliness on the gratitude-health link. (August 2016) - O'Connell, Brenda H.; O'Shea, Deirdre; Gallagher, Stephen
Abstract: The empirical study of gratitude has experienced unprecedented growth in the past decade. As such there is now a growing body of research showing the emotional, social and psychological health benefits of being grateful. More recently, emerging research is indicating that being grateful may also positively impact physical health. However, the underlying mechanisms explaining this effect are yet to be fully explored. This research examines the relationship between dispositional gratitude and self-reported physical health symptoms, and explores whether this relationship occurs because grateful individuals have fewer experiences of loneliness. In a sample of 118 adults, gratitude significantly predicted fewer physical health symptoms (sleep disturbances, headaches, episodes of respiratory infections and gastrointestinal problems) and experiences of loneliness. Simple mediation analysis revealed that the positive effect of gratitude on self-reported physical health symptoms was significantly mediated by lower reported levels of loneliness. Therefore participants who reported higher levels of gratitude, also reported lower levels of loneliness, and this then predicted better self-reported physical health symptoms. As attention to the intervening mechanisms underlying the relationship between gratitude and physical health has only begun to be investigated, the study offers novel preliminary information regarding the psychosocial mediators accounting for this association. Highlights: This study examined a psychosocial process underlying the gratitude-heath link. Gratitude significantly predicted improved physical health symptoms. This relationship between gratitude and physical health was mediated by loneliness. Gratitude leads to less loneliness and subsequently better physical health in adults.